India and the World after Covid-19: Climate Aspect - Adhikari, Nisha; Sharma, Avinash; Nath, Jagdish (Journal of Engineering, Technology, and Applied Science (JETAS), 2020)
This research ponders over the climate aspect during the Covid 19. The purpose of this is too aware and disseminate the outbreak of covid 19 cases hiking in a sky rocketing way. This study will focus on the contents of covid 19 where people are battling to overcome the hazard happening around vicinity brought by climate aspect. Its consist of information and analysis of different countries, metamorphosis of the nature with its pulchritude, tactic that need to be followed to overcome predicament, major affected tribe, initiative by various countries, climate aspect, impact at utmost level, drastic change within a smidge, crucial steps to curb COVID-19. This is also fruitful to know the behavior of nature during the COVID-19 climate change. The data were obtained through various authorized news channel and worldometers.